The effect of providing feedback on inhaler technique and adherence from an electronic audio recording device, INCA?, in a community pharmacy setting: study protocol for a randomised controlled trial. - RYDER, SHEILA; REILLY, RICHARD; BOLAND, FRANCIS; RAPCAN, VILIAM; D'ARCY, SHONA (My University, 2016)
Background: Poor adherence to inhaled medication may lead to inadequate symptom control in patients with respiratory disease. In practice it can be difficul t to identify poor adherence. We designed an acoustic recording device, the INCA® (INhaler Compliance Ass essment) device, which, when attached to an inhaler, identifies and records the time and technique of inhale r use, thereby providing objective longitudinal data on an individual ’ s adherence to inhaled medication. This study will test the hypothesis that providing objective, personalised, visual feedback on adherence to patients in combination with a tailored educational intervention in a community pharmacy se tting, improves adherence more effectively than education alone.
PUBLISHED
PMID: 27142873
Keywords: inhaled medication; inhaled medication; Next Generation Medical Devices; ADHERENCE TO THERAPY; MEDICATION COMPLIANCE; PHARMACEUTICAL CARE; Patient Compliance; community pharmacy; inhaler technique